The social return on investment of physical activity and nutrition interventions—a scoping review - Stielke, Anna; Ashton, Kathryn; Cotter-Roberts, Andrew; Dyakova, Mariana (Frontiers in Sports and Active Living, 2024)
Scarcity of resources and mounting pressures on health systems make it critical to evaluate new and existing public health interventions related to physical activity and nutrition. The Social Return on Investment (SROI) framework has gained prominence for capturing traditional variables such as economic costs and returns, as well as wider beneficial social and environmental outcomes. A scoping review was conducted to present the existing evidence on the SROI of physical activity and nutrition interventions, demonstrating the capture of the wider benefits of these interventions.Existing peer-reviewed evidence and grey literature was collated to identify physical activity and nutrition interventions that were evaluated using the SROI framework between January 1996 up until February 2022. Only literature published in the English language, interventions that were conducted in high-income countries were considered for inclusion. Study information and economic data was entered into a pre-prepared data extraction sheet and eligible studies were quality assessed using a 12-point quality assessment framework for SROI studies.This review identified a total of 21 SROI studies, with only four deriving from peer-reviewed literature sources. In total, 18 studies evaluated physical activity interventions, one study was purely focused on nutrition, whereas the two remaining studies presented a mix of physical activity and nutrition. The majority of studies derived from the United Kingdom (n=16) with very few of the studies published prior to 2010 (n=1). In total, four studies were classified as low quality based on the 12-point quality assessment framework used for this review. Outcomes of the relevant studies show that the benefits of these interventions have added value to families, communities and the wider environments of the target groups.This scoping review is adding to research conducted to understand the wider value of public health interventions such as physical activity and nutrition interventions using the SROI framework. This is important so that the development and implementation of public health interventions have the greatest value to people and society, which also benefits decision-makers to effectively and sustainably allocate scarce resources.